Negotiating historical continuities in contested terrain : a narrative-based reflection on the post-apartheid psychosocial legacies of conscription into the South African Defence Force - Edlmann, Tessa Margaret (Rhodes University, Faculty of Humanities, Department of History, 2015)
For a 25-year period during the apartheid era in South Africa, all school-leaving white men were issued with a compulsory call-up to national military service in the South African Defence Force. It is estimated that 600 000 men were conscripted between 1968 and 1993, undergoing military training and being deployed in Namibia, Angola and South Africa. The purpose of this system of military conscription was to support both the apartheid state's role in the "Border War" in Namibia and Angola and the suppression of anti-apartheid resistance within South Africa. It formed part of the National Party's strategy of a "total response" to what it perceived as the "total onslaught" of communism and African nationalism. While recruiting and training young white men was the focus of the apartheid government's strategy, all of white South African society was caught up in supporting, contesting, avoiding and resisting this system in one way or another. Rather than being a purely military endeavour, conscription into the SADF therefore comprised a social and political system with wide-ranging ramifications. The 1994 democratic elections in South Africa heralded the advent of a very different political, social and economic system to what had gone before. The focus of this research is SADF conscripts' narrations of identity in the contested narrative terrain of post-apartheid South Africa. The thesis begins with a contextual framing of the historical, social and political systems of which conscription was a part. Drawing on narrative psychology as a theoretical framework, the thesis explores discursive resources of whiteness, masculinities and perceptions of threat in conscripts' narrations of identity, the construction of memory fields in narrating memories of war and possible trauma, and the notions of moral injury and moral repair in dealing with legacies of war. Using a narrative discursive approach, the thesis then reflects on historical temporal threads, and narrative patterns that emerge when analysing a range of texts about the psychosocial legacies of conscription, including interviews, research, memoirs, plays, media reports, video documentaries, blogs and photographic exhibitions. Throughout the thesis, conscripts' and others' accounts of conscription and its legacies are regarded as cultural texts. This serves as a means to highlight both contextual narrative negotiations and the narrative-discursive patterns of conscripts' personal accounts of their identities in the post-apartheid narrative terrain. The original contribution of this research is the development of conceptual and theoretical framings of the post-apartheid legacies of conscription. Key to this has been the use of narrative-based approaches to highlight the narrative-discursive patterns, memory fields and negotiations of narrative terrains at work in texts that focus on various aspects of conscription and its ongoing aftereffects. The concept of temporal threads has been developed to account for the emergence and shifts in these patterns over time. Existing narrative-discursive theory has formed the basis for conscripts' negotiations of identity being identified as acts of narrative reinforcement and narrative repair. The thesis concludes with reflections on the future possibilities for articulating and supporting narrative repair that enables a shift away from historical discursive laagers and a reconfiguration of the narrative terrain within which conscripts narrate their identities.,Also known as: Edlmann, Theresa
Keywords: South Africa. National Defence Force; Draft -- South Africa -- History -- 20th century; Draft -- Psychological aspects; Masculinity -- South Africa; Sociology, Military -- South Africa; Whites -- Race identity -- South Africa; South Africa -- Politics and government -- 1948-1994; Narrative inquiry (Research method)